2009
DOI: 10.1007/s11368-009-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol mass transfer from field-aged sediments and subsequent biodegradation in reactors mimicking different river conditions

Abstract: Purpose Sediments can function as secondary source for water pollution of aerobically biodegradable nonhalogenated organic compounds, which are persistent in anaerobic sediments. The mass transfer of compounds from sediment to bulk water depends on hydraulic conditions. In this study, desorption, mass transfer and biodegradation are investigated under settled and resuspended sediment conditions for branched nonylphenol (NP), which was used as model compound for aerobically biodegradable and anaerobic persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Storm and flood events can cause combined sewer overflows and thereby the release of untreated wastewater, including sewage sludge particles, into surface waters (Phillips et al 2012; Madoux‐Humery et al 2013). Furthermore, remobilization of contaminants from sediments has to be considered (Eggleton and Thomas 2004; de Weert et al 2010; Müller et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Storm and flood events can cause combined sewer overflows and thereby the release of untreated wastewater, including sewage sludge particles, into surface waters (Phillips et al 2012; Madoux‐Humery et al 2013). Furthermore, remobilization of contaminants from sediments has to be considered (Eggleton and Thomas 2004; de Weert et al 2010; Müller et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…4-NPs may persist for decades in anaerobic environments (Diehl et al 2012 ), while those deposited in recent sediments may be subject to resuspension, as well as biotic and abiotic transformations. Thus, they continue to pose a serious threat to marine organisms (de Weert et al 2010 ). 4-NPs can be accumulated by aquatic organisms, especially in tissues with a high lipid content (EPA 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonylphenol biodegradation in sediments has attracted considerable attention, as it affects the potential for NP secondary pollution and food chain accumulation. , For example, Yuan et al reported that the half-lives of NP in four river sediments under oxic conditions varied from 13 to 99 d . However, a few other studies showed that NP was highly persistent in sediments, especially under anoxic or reduced conditions. ,, Shang et al detected NP in marine sediment cores near a Canadian coast which may date back to 1960s, with the estimated half-life longer than 60 years …”
Section: Introductionmentioning
confidence: 99%